Digital Marketing Dalam Upaya Peningkatan Pendonor Di UTD PMI Kabupaten Bondowoso - Azizah, Yuliatin; Amin, Saiful; Maspufah, Hayatul (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Blood services at UTD PMI Bondowoso Regency have problems due to the decreasing growth in donors. Donations also decrease every year. From the researchers' analysis, a marketing strategy for donors is needed so that donors are more active in donating. The most appropriate service strategy in the current era is a digital marketing strategy so that people better understand the importance of blood donation. Steps to resolve partner priority problems that can be carried out through the Community Partnership Program include: Expanding marketing access by carrying out integrated sales promotions through market places and digital marketing applications, socializing customer value and digital marketing, and creating a more comprehensive marketing strategy via Instagram. interesting. The implementation of community partnership program activities is to provide socialization and assistance to digital marketing management in collaboration with the Public Relations team of the Mandala Institute of Technology and Science. The output produced is UTD PMI Bondowoso Regency social media as well as scientific articles about digital marketing for UTD PMI Bondowoso Regency.